Concentric and Eccentric Endurance Exercise Reverse Hallmarks of T-Cell Senescence in Pre-diabetic Subjects - Philippe, Marc; Gatterer, Hannes; Burtscher, Martin; Weinberger, Birgit; Keller, Michael; Grubeck-Loebenstein, Beatrix; Fleckenstein, Johannes; Alack, Katharina; Krüger, Karsten (Frontiers in physiology, 2019)
The peripheral T-cell pool undergoes a striking age associated remodeling which is accelerated by progressive insulin resistance. Exercise training is known to delay several aspects of T-cell senescence. The purpose of the current study was to investigate the effect of 3 weeks regular concentric or eccentric endurance exercise training on the composition of the T-cell compartment in pre-diabetic subjects. Sixteen male older adults with impaired glucose tolerance were recruited and performed either concentric exercise (CE) or eccentric exercise (EE) walking 3 times a week for 3 weeks. Fasting venous blood sampling was performed before training and after the training intervention. Various T-cell subpopulations were analyzed by flow cytometry. We did not find significant time × group effects (interaction) but found several significant time effects for cell type ratios and cell subsets proportions. There was an increase of the CD4 /CD8 (0.55 ± 0.85%; = 0.033) and CD4 /CD3 ratio (5.63 ± 8.44%; = 0.018) and a decrease of the CD8 /CD3 ratio (-0.95 ± 1.64%; = 0.049) after training. We found proportional increases of CD4 /CCR7 /CD45RO central memory cells (5.02 ± 7.68%; = 0.030), naïve CD8 /CCR7 /CD45RO (3.00 ± 6.68%; = 0.047) and CD8 /CCR7 /CD45RO central memory cells (3.01 ± 3.70%; = 0.009), while proportions of CD4 /CCR7 /CD45RO TEMRA cells (-2.17 ± 4.66%; = 0.012), CD8 /CCR7 /CD45RO TEMRA cells (-5.11 ± 7.02%; = 0.018) and CD16 cells (-4.67 ± 6.45%; = 0.016) decreased after training. 3 weeks of either CE or EE were effective in reversing hallmarks of T-cell senescence in pre-diabetic subjects. It is suggested that exercise stimulates production and mobilization of naïve T-cells, while differentiated TEMRA cells might disappear by apoptosis.